2005
DOI: 10.3748/wjg.v11.i2.155
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic anhydrases in normal gastrointestinal tract and gastrointestinal tumours

Abstract: Carbonic anhydrases (CAs) catalyse the hydration of CO2 to bicarbonate at physiological pH. This chemical interconversion is crucial since HCO3- is the substrate for several biosynthetic reactions. This review is focused on the distribution and role of CA isoenzymes in both normal and pathological gastrointestinal (GI) tract tissues. It has been known for many years that CAs are widely present in the GI tract and play important roles in several physiological functions such as production of saliva, gastric acid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
83
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(86 citation statements)
references
References 115 publications
3
83
0
Order By: Relevance
“…Reverse transcriptase PCR revealed the presence of the AS variant in all examined tissues ( Figure 2C). In accord with the previous studies, FL transcript was found only in the normal stomach and in tumours derived from the colon and rectum (Saarnio et al, 1998;Kivela et al, 2005).…”
Section: Expression Of Human As Ca IX In Tumour Cell Lines and Tissuessupporting
confidence: 91%
See 1 more Smart Citation
“…Reverse transcriptase PCR revealed the presence of the AS variant in all examined tissues ( Figure 2C). In accord with the previous studies, FL transcript was found only in the normal stomach and in tumours derived from the colon and rectum (Saarnio et al, 1998;Kivela et al, 2005).…”
Section: Expression Of Human As Ca IX In Tumour Cell Lines and Tissuessupporting
confidence: 91%
“…Human tissues were selected from the collection described previously (Kivela et al, 2005). M75 and V/10 mouse MAbs specific for the human MN/CA IX protein were characterised earlier (Pastorekova et al, 1992;Zatovicova et al, 2003).…”
Section: Cell Culture Tissues and Antibodiesmentioning
confidence: 99%
“…Multiple studies have analyzed the organ-specific expression of Car1 (12,13,16,17). In the gastrointestinal tract, Car1 is expressed in the colon but not in the small intestine, with highest expression in the proximal colon (16).…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of H&E-stained slides, a neuropathologist (H. Haapasalo) did an evaluation of the tumors according to the WHO 2000 criteria (12). These criteria divide diffusely infiltrating astrocytomas into three grades (2)(3)(4) according to the presence of atypia, mitotic activity, necrosis, and endothelial proliferation. The neuropathologist pinpointed one histologically representative tumor region in each sample specimen.…”
Section: Methodsmentioning
confidence: 99%